Dynamics of Interpersonal Communication among Children with ADHD - Deta Febrianty; Lusiana Suciati Dewi (Lembaga Pengembangan Kinerja Dosen, 2024)
The study aims to analyze the speech patterns of children who have hyperactivity disorders in the classroom context. The observational approach is used in this study to learn how the children respond to the instructions given. Children with adhd tend to have difficulty understanding complex instructions, so researchers need to highlight appropriate communication patterns and avoid giving them overly complex instructions. Interactions start with conversations between language researchers and communicative behaviors, so that children with adhd can more readily understand the content of a conversation and respond favorably. The study uses descriptive qualitative research methods. The data-gathering technique used was the triangulation or fusion of observation, interviews, and documentation. The results of this study show difficulties in maintaining attention, as well as difficulties in understanding and following instructions given in conversation in children with ADHD. These observation activities provide new insights into the children's behavior and characteristics with adhd, as well as proper treatment measures to meet their needs in social interaction.